(untitled) (Research, Society and Development, 2023)
This bibliographic and documentary research aimed to analyze the representations of Black women in the Science textbooks of PNLD/2017, used in the municipal public education system of Itapiúna, Ceará. Focusing on the collection “Natural Sciences: Learning from Everyday Life,” the iconographies of the covers, unit openings, and related images were examined, using references such as Opinion 03/CNE/CP/2004, Chartier and categories like race racism, prejudice, racial discrimination, and Black identity. The research is a segment of a completed master’s study in 2021, within the Interdisciplinary Graduate Program in Humanities at Unilab-CE, using Bardin’s Conten Analysis. The obtained results demonstrate a low representation of Black women followed by a more frequent portrayal of white women in the analyzed collection. Furthermore, the investigation observed a pinpoint “alignment” of imagery representations of Black women with respect to the three principles outlined in Opinion CNE/CP 003/2004: “political and historical awareness of diversity,” “strengthening identities and rights,” and “educational actions against racism and discrimination”.